Indonesian Gastronomy (Volumes 1 and 2) - Agus Trihartono; Budhy Santoso; Himawan Bayu Patriadi (Pusbindiklatren Bappenas, 2022)
The books “Indonesian Gastronomy Volumes 1 and 2,” written by Professor Murdijati-Gardjito and colleagues, are interesting because they are among the first gastronomic books authored by experts in Food Science and Technology. While representing a coherent work, the two volumes focus on different aspects. The first one explains aspects of Indonesian culinary history at the national and global levels, including the changes that have taken place in the contemporary era. The second volume pays attention to the technical aspects of physical changes and chemical reactions in the food-making process. Volume 2 also describes Indonesian cuisine based on geographical location and ethnic affiliation.